Fair retail banking: How to prevent mis-selling by banks - Günter Franke; Thomas Mosk; Eberhard Schnebel (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2016)
Mis-selling by banks has occurred repeatedly in many nations over the last decade. While clients may benefit from competition - enabling them to choose financial services at lowest costs - economic frictions between banks and clients may give rise to mis-selling. Examples of mis-selling are mis-representation of information, overly complex product design and non-customized advice. European regulators address the problem of mis-selling in the "Markets in Financial Instruments Directive" (MiFID) I and II and the "Markets in Financial Instruments Regulation" (MiFIR), by setting behavioral requirements for banks, regulating the compensation of employees, and imposing re-quirements on offered financial products and disclosure rules. This paper argues that MiFID II protects clients but is not as effective as it could be. (1) It does not differentiate between client groups with different levels of financial literacy. Effective advice requires different advice for different client groups. (2) MiFID II uses too many rules and too many instruments to achieve identical goals and thereby generates excessive compliance costs. High compliance costs and low revenues would drive banks out of some segments of retail business.
urn:nbn:de:hebis:30:3-412367
Keywords: 330; retail banking; mis-selling; MiFID II